A survey on the development of Islamic higher education in Indonesia: an epistemological review (State Institute of Islamic Studies (STAIN) Salatiga, 2011)
Social changes, development and advancement of humansâ culture influence educationas inseparable aspect of human life. In line with Islamic higher educationmany thinkers proposed their ideas of how to formulate its appropriate epistemologicalbackground in different views. There are some notable persons forthis field, such as Iqbal, Fazlur Rahman, Afzalur Rahman, Al-Faruqi which tosome extent parallel or influence Indonesian thinkersâ such as Mukti Ali, HarunNasution, Cak Nur, Amin Abdullah, etc. Some are still at the level of speculativethought, while others have applied their ideas in educational institutions, likeAmin Abdullah and Imam Suprayoga.Perubahan sosial, perkembangan dan kemajuan kebudayaan umat manusiamemengaruhi pendidikan yang merupakan bidang yang tak terpisahkan darikehidupan manusia itu sendiri. Dalam hal pendidikan tinggi Islam, para pemikirmengajukan berbagai gagasan mereka tentang bagaimana merumuskan dasardasarepistemologinya yang paling tepat. Ada beberapa tokoh pemikir pentingyang perlu dicatat (dari luar negeri) dalam hal ini seperti Iqbal, Fazlur Rahman, Afzalur Rahman, al-Faruqi, yang dalam batas tertentu secara paralel ataumemengaruhi para pemikir Indonesia seperti Mukti Ali, Harun Nasution, Cak Nur,Amin Abdullah dan Imam Suprayoga. Sebagian dari pemikir tersebut masih padadataran pemikiran spekulatif, sementara yang lain sudah mengaktualisasikannyadalam implementasi kelembagaan pendidikan tinggi Islam, seperti Amin Abdullahdan Imam Suprayoga.